Smoltification status of Atlantic salmon (Salmo salar) in relation to migratory success and migration speed in a regulated river - Högvall, Johanna (Karlstads universitet, 2020)
There is a concern that the ecosystems around the world are suffering from fragmentation. Ecosystems such as rivers have lost their connectivity to a large extent due to hydroelectric dams with no or insufficient passways for the natural flow of organisms, matter and energy. The Atlantic salmon, Salmo salar, is anadromous, migrating up rivers to spawn as adults and downstream to the sea as juveniles to feed. Before entering the sea, juveniles go through a parr-smolt transformation which alters their behavior, morphology, and physiology. Using radio telemetry, we assessed how the degree of smoltification, in combination with migrational timing and the juvenile’s size, affected their migration. Overall migratory success was found to differ significantly across the range of smoltification, with more fully smoltified juveniles having the highest probability (94%) of reaching the sea. No relationship was found between smoltification status and average migrational speed or delays when passing a dam. Migrational timing was also correlated to migrational success, with earlier juveniles being 50 % more likely to reach the sea than those leaving 2-3 weeks later. All of the tagged juveniles (28) that passed the dam were delayed by an average of 1,32 km/h relative to their median speed in the river, and 18 of the juveniles made it down to the sea. No effect of migrational timing was found with average migrational speed or with dam delays however. Unexpectedly, larger lengths were correlated with slower average migration speeds and greater delays when encountering a dam. This new knowledge about the degree of smoltification and its relation to migration success can help river management to direct their efforts in the right direction to strengthen salmon populations. Ekosystem som älvar och åar har i stor utsträckning förlorat konnektiviteten till följd av vattenkraftverk med otillräckliga passager för det naturliga flödet av organismer, materia och energi. Atlantlax Salmo salar är en anadrom fisk vars livscykel kräver att ...